Value Changes in Ontario Education Act: A Narrative and Discussion - Li, Xiaobin (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation, 2026)
The purpose of this article is to examine value changes in the Education Act (1990) of Ontario, Canada, since 1807 when the Public Schools Act (1807) became the first education legislation in the province. With three main sections in the article, the first section offers a brief historical background of the Education Act (1990) from its beginning in 1807 to 1995, when the Conservatives reformed the governance of education in Ontario following their political values. The second section describes the value changes in the Education Act (1990) and related legislation that the Conservatives, the Liberals, and the Conservatives again have made since 1995. The third section discusses and reflects on the value changes described. The methodology of the study was document analysis, focusing on values reflected in legal documents and the relevant literature. The paper attempts to provide an interpretation of the value changes reflected in the Education Act (1990), its predecessors, and related legislation, as well as their implications for educational administration.